Work ethics and general work attitudes in adolescents are related to quality of life, sense of coherence and subjective health - a Swedish questionnaire study - Håkansson Anders; Andersson Ingemar; Axelsson Lars; Ejlertsson Göran (BMC, 2005)
Abstract Background Working life is an important arena in most people's lives, and the working line concept is important for the development of welfare in a society. For young people, the period before permanent establishment in working life has become longer during the last two decades. Knowledge about attitudes towards work can help us to understand young people's transition to the labour market. Adolescents are the future workforce, so it seems especially important to notice their attitudes towards work, including attitudes towards the welfare system. The aim of this study was to describe and analyse upper secondary school students' work attitudes, and to explore factors related to these attitudes. Methods The sample consisted of 606 upper secondary school students. They all received a questionnaire including questions about quality of life (QOL), sense of coherence (SOC), subjective health and attitudes towards work. The response rate was 91%. A factor analysis established two dimensions of work attitudes. Multivariate analyses were carried out by means of logistic regression models. Results Work ethics (WE) and general work attitudes (GWA) were found to be two separate dimensions of attitudes towards work. Concerning WE the picture was similar regardless of gender or study programme. Males in theoretical programmes appeared to have more unfavourable GWA than others. Multivariate analyses revealed that good QOL, high SOC and good health were significantly related to positive WE, and high SOC was positively related to GWA. Being female was positively connected to WE and GWA, while studying on a practical programme was positively related to GWA only. Among those who received good parental support, GWA seemed more favourable. Conclusion Assuming that attitudes towards work are important to the working line concept, this study points out positive factors of importance for the future welfare of the society. Individual factors such as female gender, good QOL, high SOC and good health as well as support from both parents, positive experience of school and work contacts related positively to attitudes towards work. Further planning and supportive work have to take these factors into account.